2005
DOI: 10.1038/sj.onc.1208620
|View full text |Cite
|
Sign up to set email alerts
|

In Ewing's sarcoma CCN3(NOV) inhibits proliferation while promoting migration and invasion of the same cell type

Abstract: Altered expression of CCN3 has been observed in a variety of musculoskeletal tumours, including Ewing's sarcoma (ES). Despite its widespread distribution, very little is known about its biological functions and molecular mechanisms of action. We transfected CCN3 gene into a CCN3-negative ES cell line and analysed the in vitro and in vivo behaviours of stably transfected clones. Forced expression of CCN3 significantly reduced cell proliferation in vitro, growth in anchorage-independent conditions, and tumorigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 47 publications
(57 reference statements)
8
92
3
Order By: Relevance
“…In effect, here CCN5 along with CCN3 as another example, functions as the brakes for the CCN family where the other CCN proteins may act as drivers. In fact, a similar relationship had been gleaned from previous studies on other CCN proteins, like CCN3 (note CCN6 later on), which showed growth inhibitory properties ex vivo and anti tumor effects in vivo in glioblastoma (Gupta et al 2001), choriocarcinomas (Gellhaus et al 2004) and Ewing's sarcoma (Benini et al 2005), with interaction by other CCN members. The scenario is very much like other signaling intermediates, e.g.…”
Section: Ccn5 (Wisp-2)mentioning
confidence: 72%
See 1 more Smart Citation
“…In effect, here CCN5 along with CCN3 as another example, functions as the brakes for the CCN family where the other CCN proteins may act as drivers. In fact, a similar relationship had been gleaned from previous studies on other CCN proteins, like CCN3 (note CCN6 later on), which showed growth inhibitory properties ex vivo and anti tumor effects in vivo in glioblastoma (Gupta et al 2001), choriocarcinomas (Gellhaus et al 2004) and Ewing's sarcoma (Benini et al 2005), with interaction by other CCN members. The scenario is very much like other signaling intermediates, e.g.…”
Section: Ccn5 (Wisp-2)mentioning
confidence: 72%
“…The CCN3 link with prognosis in osteosarcoma and Ewing's tumors in patients has been previously reported Manara et al 2002). In Ewing's sarcoma, CCN3 plays a dual role, inhibiting proliferation while promoting migration and invasion of the same cells (Benini et al 2005). In comparison, melanomas overexpressing CCN3 show a higher metastatic potential studied as xenografts (Vallacchi et al 2008), while overexpression of CCN3 in human prostate cell lines (Maillard et al 2001) and high expression in high grade renal cell carcinomas (Glukhova et al 2001) favor an active role in tumorigenesis and progression.…”
Section: Ccn3 (Nov)mentioning
confidence: 99%
“…6a and b). It has been well established that overexpression of CCN3 promotes cell migration in different cancer cells (Benini et al 2005) and that CCN3/ NOV increases the activity of the small GTPase Rac1, revealing a pathway directly linking Cx43 to actin reorganization (Sin et al 2009). CCN3/NOV siRNA is able to attenuate gap closing in monolayer cell scratchinduced migration indicating that NOV/CCN3 promotes cell migration.…”
Section: Resultsmentioning
confidence: 99%
“…CCN3 also modulates cell adhesion and migration (Benini et al 2005), and CCN3 expression in primary Ewing's tumors was associated with higher risk of developing metastasis (Manara et al 2002). These results suggest a critical role for CCN3 in cancer progression.…”
Section: Introductionmentioning
confidence: 83%